Effects of Aerobic Exercise on Serum Retinol Binding Protein4, Insulin Resistance and Blood Lipids in Obese Women. - Farzaneh Taghian; Maryam Zolfaghari; Mehdi Hedayati (Tehran University of Medical Sciences, 2014)
Retinol binding protein4 (RBP4) is a type of adipokine which transports vitamin A to serum. RBP4 could be a bridge between obesity and insulin resistance. This study aimed to investigate the effects of aerobic exercises on RBP4 serum's concentration and metabolic syndrome risk factors in obese women.Twenty obese women with body max index 35.81±3.67Kg/m2, fat percentage 43.98±4.02, and waist to hip ratio 1.03±0.05 were included and were randomly assigned to experimental and control groups. The experimental group received aerobic exercises for a period of 12 weeks each three sessions on treadmill workout. The treadmill speed were based on a 60-65 and 80-85 maximal heart rate percentage and duration of 15-20 and 45-50 minutes, at the beginning and the end of exercise, respectively. Body composition, serum glucose, insulin, TG, LDL-C, HDL-C, total cholesterol, and RBP4, were measured in both groups before and after the treatment by ELISA method. Insulin resistance was measured by HOMA-IR. To compare within group differences and between group comparisons t-correlated and t-independent tests were used, respectively.After 12 week aerobic exercises; weight, fat percentage, WHR, and BMI in the experimental group was significantly decreased (P